2008
DOI: 10.1159/000167844
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Influence of Doxazosin and Finasteride in Benign Prostatic Hyperplasia Accompanying Chronic Inflammation

Abstract: Aim: To evaluate the influence of doxazosin and finasteride on histologic findings in benign prostatic hyperplasia accompanied by prostatitis, and to examine the factors related with prostate carcinogenesis. Materials and Methods: Prostate tissue from 17 cases of prostatic hyperplasia were divided into three groups; group 1: no medication history, group 2: both doxazosin and finasteride for at least 6 months before surgery; group 3: doxazosin for a minimum of 6 months before transurethral resection. Formalin-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…Just like that hypoxia and angiogenesis are common findings in human BPH tissue [33,34], our EAP model successfully simulated BPH-related pathological conditions such as chronic inflammatory cell infiltration, hypoxia, and angiogenesis. On the other hand, it has been reported that reduced apoptosis often occurs in inflamed atrophic lesions [35,36], which may involve the potential carcinogenic effects of chronic or recurrent inflammation [18]. Although there is no evidence that human BPH will progress to prostate cancer, a reduction in apoptosis in the EAP rat prostates of this study was observed, and KLK1 administration restored the level of apoptosis of them.…”
Section: Discussioncontrasting
confidence: 53%
“…Just like that hypoxia and angiogenesis are common findings in human BPH tissue [33,34], our EAP model successfully simulated BPH-related pathological conditions such as chronic inflammatory cell infiltration, hypoxia, and angiogenesis. On the other hand, it has been reported that reduced apoptosis often occurs in inflamed atrophic lesions [35,36], which may involve the potential carcinogenic effects of chronic or recurrent inflammation [18]. Although there is no evidence that human BPH will progress to prostate cancer, a reduction in apoptosis in the EAP rat prostates of this study was observed, and KLK1 administration restored the level of apoptosis of them.…”
Section: Discussioncontrasting
confidence: 53%
“…Vignozzi et al highlighted that DHT exerts an immune regulatory role on human prostatic stromal cells, inhibiting their potential to actively induce and/or sustain autoimmune and inflammatory responses [27]. Park and Shim found that finasteride might interfere with the anti-inflammatory reaction induced by doxazosin in combination of doxazosin and finasteride treatment [28]. Here we detected more patients and identified the T cell subsets which infiltrated in the prostatic tissue after finasteride treatment.…”
Section: Discussionmentioning
confidence: 69%
“…In contrast, another study in a mouse model of BPH showed that finasteride increased persistent PIS (i.e., CD45 + cell foci) [ 36 ]. In a study of 17 patients with BPH undergoing transurethral resection of the prostate (TURP), doxazosin ( N = 4) reduced the staining of CD3 and CD68 compared to no treatment ( N = 5) [ 37 ]. Glutathion-S-transferase pi-1 (GSTP1: inactivates oxidant carcinogens) expression was only decreased in patients receiving both doxazosin and finasteride ( N = 8) suggesting that finasteride may interfere with the anti-inflammatory effect of doxazosin.…”
Section: Methodsmentioning
confidence: 99%